Peran Tax Planning, Deferred Tax Expense, dan Profitabilitas dalam Mendorong Manajemen Laba pada PerusahaanTerdaftar di BEI - Hamdani, Azzra Faqih; Nawangsari, Ajeng Tita (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to examine the role of tax planning, deferred tax expense, and profitability in influencing earnings management among companies listed on the Indonesia Stock Exchange. Utilizing secondary financial statement data over a three-year observation period and employing multiple linear regression, this research provides empirical insights into how tax-related factors and financial performance shape reported earnings. The findings reveal that tax planning has a negative and significant effect on earnings management, indicating that effective tax strategies reduce the managerial incentive to manipulate earnings. In contrast, deferred tax expense exhibits a positive and significant influence, supporting the notion that temporary tax differences often serve as an avenue for managerial discretion in adjusting reported income. Profitability also shows a negative and significant effect, suggesting that firms with stronger financial performance have fewer motivations to engage in earnings manipulation. Collectively, the three variables explain nearly half of the variation in earnings management, underscoring the importance of tax attributes and profitability in determining the quality of financial reporting among publicly listed firms.